A carbosulfan insecticide to protect pine seedlings from Hylastes ater (Coleoptera Scolytidae) damage - Reay, S.D.; Walsh, P.J. (New Zealand Plant Protection, 2002)
A controlled release granular carbosulfan pesticide was tested for efficacy against Hylastes ater damage of Pinus radiata seedlings in secondrotation forests in the central North Island Our study involved control seedlings and seedlings treated with 10 g or 15 g carbosulfan granules per seedling Seedling mortality ranged from 0 to 8 at the five sites When seedling mortality was high (8) mortality was reduced to 07 and 0 for carbosulfan granules applied at 10 g/seedling and 15 g/seedling respectively While seedling mortality in the five sites was low a large proportion of seedlings were damaged (38 to 83 of untreated seedlings) by H ater Untreated seedlings were damaged more frequently and with greater severity than treated seedlings The results indicate that that carbosulfan should protect P radiata seedlings from damage caused by H ater when used at the recommended field rate